(What Geographers Should Know About) The State of U.S. and Canadian Academic Professional Associations' Engagement with Mental Health Practices and Policies. Issue 1 (2nd January 2020) - Peake, Linda J.; England, Kim
Abstract : The professional organizations to which geographers belong and by which they are represented have a civic duty and ethical responsibility to educate their members about mental health issues in their professions and, by default, their work environments. And yet national-level professional associations in North America are lagging behind universities in adopting initiatives, commissioning reports, and looking into best practices around the mental health of their members. A survey of the Web sites of sixty-six professional associations in the social sciences, geographical sciences, and humanities in the United States and Canada reveals an uneven presence of attention to mental health issues in terms of their members' research on mental health issues, awareness of mental health as a professional development issue, and engagement in mental health advocacy and public outreach. In this article, we explore how geography's professional organizations compare to others with respect to these issues and suggest ways in which they can develop their own mental health protocols to address the crisis of mental health in the academy. Key Words: Academic professional associations, American Association of Geographers, Canadian Association of Geographers, mental health, mental health practices and policies.